DIETARY PATTERNS IN PREVENTION OF CHRONIC NON-COMMUNICABLE DISEASES: CURRENT FINDINGS - Škorić, Dragana; Vasiljevic, Nadja (Medicinski podmladak, 2024)
Dietary patterns are currently intensively studied, since they take into account interactions of different foods during intake and give a more comprehensive overview on the health impact compared to studying the individual foods’ and nutrients’ intake. They are also important considering their contribution to the etiology of chronic non-communicable diseases. The two most common methods of their assessment are calculation of indices and data processing through statistical methods. It has been shown that the Mediterranean diet, the DASH diet, as well as plant-based healthy dietary patterns have the greatest beneficial effect in the prevention of cardiovascular diseases, and there is increasing evidence of the beneficial effect of the Nordic and traditional Asian diets. The Mediterranean diet is also associated with a reduced risk of developing type 2 diabetes, while an unhealthy, Western diet is associated with an increased risk. The Mediterranean diet combined with reduced energy intake and regular physical activity is considered to be the most effective approach for body weight loss and control. It is considered the gold standard for the prevention of non-alcoholic fatty liver disease, and it is also recommended for the prevention of depression. Adherence to the MIND diet has been described as being associated with a reduced risk of developing Alzheimer’s disease and a slower decline in cognitive function, and diets such as the Mediterranean, DASH and Japanese diets, have also been shown to be beneficial. A Mediterranean-like diet is also advised in the literature to reduce the risk of fractures. Plant-based diets are also associated with a reduced risk of cancer. Despite a lot of evidence of significant effects of certain dietary patterns, especially those that are plant-based, in chronic non-communicable diseases’ prevention, further research is needed to reach valid conclusions about their effects, especially in some less studied chronic non-communicable diseases.